1999
DOI: 10.1074/jbc.274.46.32988
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Casein Kinase 2 Subunits in Chinese Hamster Ovary and 3T3 L1 Cells Provides Information on the Role of the Enzyme in Cell Proliferation and the Cell Cycle

Abstract: In order to investigate the in vivo functions of protein kinase CK2 (CK2), the expression of Myc-tagged versions of the subunits, Myc-CK2␣ and Myc-CK2␤, was carried out in Chinese hamster ovary cells (CHO cells) and in 3T3 L1 fibroblasts. Cell proliferation in these cells was examined. CHO 3 H]thymidine incorporation, it was found that expression of Myc-CK2␤ prolonged the G 1 phase and inhibited up-regulation of cyclin D1 expression during G 1 . In addition, a lower mitotic index and lower mitotic cyclin-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 43 publications
4
49
7
Order By: Relevance
“…With this conventional view, it might be therefore predicted that autophosphorylated CK2b only exists within tetrameric CK2 complexes. However, a mounting body of evidence indicates that CK2b has functions that are independent of its role in CK2 complexes (Boldyre and Issinger, 1997;Li et al, 1999;Toczyski et al, 1997;Teitz et al, 1990). The three-dimensional structure of tetrameric CK2 that has emerged from X-ray crystallography also challenges the traditional view that CK2 complexes are stable tetramers (Nie®nd et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…With this conventional view, it might be therefore predicted that autophosphorylated CK2b only exists within tetrameric CK2 complexes. However, a mounting body of evidence indicates that CK2b has functions that are independent of its role in CK2 complexes (Boldyre and Issinger, 1997;Li et al, 1999;Toczyski et al, 1997;Teitz et al, 1990). The three-dimensional structure of tetrameric CK2 that has emerged from X-ray crystallography also challenges the traditional view that CK2 complexes are stable tetramers (Nie®nd et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…In mammalian cells, a possible role for CK2 at G2/M has been suggested from results of various experimental approaches. In 3T3 L1 fibroblast cells, the increased expression of CK2b was shown to cause accumulation in G2/M, suggesting a role of CK2 at this point of the cell cycle (Li et al, 1999). Furthermore, both types of CK2 subunits can be phosphorylated by CDK1 in vitro and in intact cells during mitosis (Litchfield et al, 1992;Bosc et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CK2b can inhibit the activity of c-Mos preventing Xenopus oocytes maturation (Chen et al, 1997). Moreover, the transient or the stable ectopic expression of Myc-tagged CK2b inhibits cell proliferation and reduces mitotic cyclin-dependent kinases activity (Li et al, 1999). In S. cerevisiae, CK2b has been implicated in checkpoint regulation (Toczyski et al, 1997).…”
Section: Introductionmentioning
confidence: 99%